Current assessment and management of endoleaks after advanced EVAR: new devices, new endoleaks?. (2nd August 2020) - Cannavale, Alessandro; Lucatelli, Pierleone; Corona, Mario; Nardis, Piergiorgio; Cannavale, Giuseppe; De Rubeis, Gianluca; Santoni, Mariangela; Maher, Ben; Catalano, Carlo; Bezzi, Mario
ABSTRACT: Introduction: In recent years there has been an increasing application of advanced EVAR techniques to tackle complex clinical and anatomical scenarios. In a bid to overcome the limitations of the traditional stent-grafts, newer EVAR endografts and techniques have been developed and introduced into clinical practice, permitting endovascular management of difficult infrarenal, juxta-renal and thoracoabdominal aneurysms for which previously there was no endovascular solution. As a consequence, we are now confronted with unique patterns of endoleak requiring customized clinical-radiological assessment and treatment. Despite the increasing body of evidence regarding new EVAR techniques and related endoleaks, current guidelines do not specifically address these issues. Objectives: Our review aims to assess risk factors, development, and management strategies of these endoleaks, in the most recent infrarenal EVAR devices and in more complex fenestrated EVAR (FEVAR) and Chimney EVAR (Ch-EVAR). Expert opinion: Most new devices have demonstrated types of endoleaks that need specific imaging and treatment, as in EVAS, FEVAR, and ChEVAR. Knowledge of specific stent-graft characteristics and the nature of endoleaks associated with the various procedures facilitates the application of relevant useful imaging. In addition, it should aid development of a customized and practically relevant approach to patient management during intervention and follow-up.